Contrast Extravasation on CT Predicts Mortality in Primary Intracerebral Hemorrhage - Kim, J.; Smith, A.; Hemphill, J.C.; Smith, W.S.; Lu, Y.; Dillon, W.P.; Wintermark, M. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Recent studies of intracerebral hemorrhage (ICH) treatments have highlighted the need to identify reliable predictors of hematoma expansion. The goal of this study was to determine whether contrast extravasation on multisection CT angiography (CTA) and/or contrast-enhanced CT (CECT) of the brain is associated with hematoma expansion and increased mortality in patients with primary ICH.MATERIALS AND METHODS: All patients with primary ICH who underwent CTA and CECT, as well as follow-up noncontrast CT (NCCT) before discharge/death from January 1, 2003, to September 30, 2005, were retrospectively identified. One neuroradiologist reviewed admission and follow-up NCCT for hematoma size and growth. A second neuroradiologist independently reviewed CTA and CECT for active contrast extravasation. Univariate and multivariate logistic regression analyses were performed to evaluate the significance of clinical and radiologic variables in predicting 30-day mortality, designated as the primary outcome. Hematoma growth was considered as a secondary outcome.RESULTS: Of 56 patients, contrast extravasation was seen in 17.9% of patients on initial CTA and in 23.2% of patients on initial CECT following CTA. Univariate analysis showed that the presence of extravasation on CT, large initial hematoma size (>30 mL), the presence of “swirl sign” on NCCT, the Glasgow Coma Scale and ICH scores, and international normalized ratio were associated with increased mortality. On multivariate analysis, only contrast extravasation on CT (P = .017) independently predicted mortality. Contrast extravasation on CT (P < .001) was also an independent predictor of hematoma growth on multivariate analysis.CONCLUSION: Active contrast extravasation on CT in patients with primary ICH independently predicts mortality and hematoma growth.